Electrotransformation and Clonal Isolation of Rickettsia Species. Issue 1 (3rd November 2015) - Riley, Sean P.; Macaluso, Kevin R.; Martinez, Juan J.
Abstract: Genetic manipulation of obligate intracellular bacteria of the genus Rickettsia is currently undergoing a rapid period of change. The development of viable genetic tools, including replicative plasmids, transposons, homologous recombination, fluorescent protein‐encoding genes, and antibiotic selectable markers has provided the impetus for future research development. This unit is designed to coalesce the basic methods pertaining to creation of genetically modified Rickettsia . The unit describes a series of methods, from inserting exogenous DNA into Rickettsia to the final isolation of genetically modified bacterial clones. Researchers working towards genetic manipulation of Rickettsia or similar obligate intracellular bacteria will find these protocols to be a valuable reference. © 2015 by John Wiley & Sons, Inc.